Exposure to secondhand tobacco smoke and lung cancer by histological type: A pooled analysis of the International Lung Cancer Consortium (ILCCO). Issue 8 (25th March 2014) - Kim, Claire H.; Lee, Yuan‐Chin Amy; Hung, Rayjean J.; McNallan, Sheila R.; Cote, Michele L.; Lim, Wei‐Yen; Chang, Shen‐Chih; Kim, Jin Hee; Ugolini, Donatella; Chen, Ying; Liloglou, Triantafillos; Andrew, Angeline S.; et al.
<x xml:space="preserve">Abstract</x> While the association between exposure to secondhand smoke and lung cancer risk is well established, few studies with sufficient power have examined the association by histological type. In this study, we evaluated the secondhand smoke‐lung cancer relationship by histological type based on pooled data from 18 case–control studies in the International Lung Cancer Consortium (ILCCO), including 2, 504 cases and 7, 276 control who were never smokers and 10, 184 cases and 7, 176 controls who were ever smokers. We used multivariable logistic regression, adjusting for age, sex, race/ethnicity, smoking status, pack‐years of smoking, and study. Among never smokers, the odds ratios (OR) comparing those ever exposed to secondhand smoke with those never exposed were 1.31 (95% CI: 1.17–1.45) for all histological types combined, 1.26 (95% CI: 1.10–1.44) for adenocarcinoma, 1.41 (95% CI: 0.99–1.99) for squamous cell carcinoma, 1.48 (95% CI: 0.89–2.45) for large cell lung cancer, and 3.09 (95% CI: 1.62–5.89) for small cell lung cancer. The estimated association with secondhand smoke exposure was greater for small cell lung cancer than for nonsmall cell lung cancers (OR=2.11, 95% CI: 1.11–4.04). This analysis is the largest to date investigating the relation between exposure to secondhand smoke and lung cancer. Our study provides more precise estimates of the impact of secondhand smoke on the major histological types of lung cancer, indicates the association with secondhand smoke is stronger for small cell lung cancer than for the other histological types, and suggests the importance of intervention against exposure to secondhand smoke in lung cancer prevention.